Accumulation of High‐Molecular‐Weight Glutenin Subunits in Superior and Inferior Grains of a Winter Wheat, Yangmai 158. Issue 3 (5th December 2016) - Hoang, Kimtoan; Li, Xiangnan; Bo, Yun; Zhou, Qin; Cai, Jian; Wang, Xiao; Cai, Hua; Dai, Tingbo; Cao, Weixing; Jiang, Dong
Abstract : The difference in accumulation of high‐molecular‐weight glutenin subunits (HMW‐GS) in superior (basal) and inferior (distal) grains results in the nonuniformity of grain quality in a winter wheat ( Triticum aestivum L. 'Yangmai 158'). The HMW‐GS accumulation and glutenin macropolymer (GMP) content were studied in superior and inferior grains during the grain‐filling period. Compared with inferior grains, HMW‐GS was formed earlier and total accumulation amount was higher in superior grains. The total HMW‐GS content was higher in superior grain than inferior grain, except at maturity. For individual HMW‐GS types, the accumulation and content of subunit 7 were the highest, followed by subunit 12, and those of subunit 8 were the lowest, followed by subunit 2 in superior grain. In contrast, the accumulation and content of subunit 7 at maturity were significantly higher than subunit 8 but similar between subunit 2 and subunit 12 in inferior grain. Moreover, the accumulation of subunit 7 and 12 in superior grain was significantly higher than in inferior grain. However, compared with the inferior grain, the GMP accumulation was higher but content was lower in superior grain at maturity.